2018
DOI: 10.1136/bmjopen-2017-017111
|View full text |Cite
|
Sign up to set email alerts
|

Realist evaluation of a complex integrated care programme: protocol for a mixed methods study

Abstract: IntroductionThe lack of understanding of how complex integrated care programmes achieve their outcomes due to the lack of acceptable methods leads to difficulties in the development, implementation, adaptation and scaling up of similar interventions. In this study, we evaluate an integrated care network, the National University Health System (NUHS) Regional Health System (RHS), consisting of acute hospitals, step down care, primary care providers, social services and community partners using a theory-driven re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 33 publications
1
46
0
1
Order By: Relevance
“…In cases of social (health) reform, determining the control group is difficult, and policy research may encounter threats to both internal and external validity [43]. Many other methodologies have been developed and applied in health care policy experimentation [44], such as realist evaluation [45] and contribution analysis [46]. Discussions in these domains are still underway as these methodologies each have their own strengths and challenges.…”
Section: Empirical Challengesmentioning
confidence: 99%
“…In cases of social (health) reform, determining the control group is difficult, and policy research may encounter threats to both internal and external validity [43]. Many other methodologies have been developed and applied in health care policy experimentation [44], such as realist evaluation [45] and contribution analysis [46]. Discussions in these domains are still underway as these methodologies each have their own strengths and challenges.…”
Section: Empirical Challengesmentioning
confidence: 99%
“…In our evaluation study [6], the number of lives saved was found to have improved [7]. Cost-utility analysis measures more aspects of health and well-being but was not appropriate without findings demonstrating improvements in health-related quality of life.…”
Section: Introductionmentioning
confidence: 79%
“…A realist evaluation includes a contextual evaluation (in what circumstances),37 a process evaluation (what works for whom)38 and outcomes evaluation (how). This holistic evaluation approach makes realist evaluation framework an ideal candidate to deal with the uncertainty and the complexity of interventions in medical informatics 39 40…”
Section: Methodsmentioning
confidence: 99%